Pathological skin picking: case presentation and review of the literature - Maria Isabela Sarbu; Mircea Tampa; Diana Leahu; Cristina Raileanu; Vasile Benea; Simona Roxana Georgescu (Journal of Mind and Medical Sciences)
Pathological skin picking is a condition in which patients induce skin lesions through repetitive, compulsive excoriations of normal skin or skin with minor surface irregularities and they admit their role in the production of the lesions, but are unable to stop their behavior. Psychiatric comorbidities most often associated with skin picking include obsessive-compulsive disorder (OCD), anxiety disorders, mood disorders, body dysmorphic disorders, trichotillomania and compulsive-buying disorder. We report the case of a 17 year old female patient who addressed the dermatology department of our hospital with an eruption consisting of erythematous papules and plaques. The local examination revealed several clues of paramount importance in drawing the final conclusion and the psychiatric examination helped establish the diagnosis of pathological skin picking in a patient with obsessive-compulsive disorder.